DEVELOPMENT OF MODEL SETTING VOLLEYBALL FOR JUNIOR HIGH SCHOOL - AINI, KHUROTUL (JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2016)
The aim of this research is to produce development of model setting volleyball for junior high school. In addition, this research was conducted to obtain further information about: the development and application of model setting volleyball for junior high school, and knowing the effectiveness, efficiency and appeal of the development of model setting volleyball for junior high school. The design of this research was using Borg and Gallâs Research and Developmental model.The instrument used in this research were questionnaires to collect the data on: (1) need assessment, (2) evaluation from experts (initiation product evaluation), (3) limited trial (trial in small group); and (4) the main trial (field testing). The result of model setting volleyball between pretest and posttest has tOscore = 4.512 more than tt score= 1,796, so the null hypothesis was rejected, and the mean of pretest score (x1) = 12.67 smaller than the mean of posttest score (x2) = 13.92Based on the results of this research can be concluded that: (1) with development of model setting volleyball for junior high school, students can learn effectively and efficiently (2) with the development of model setting volleyball for junior high school that has been develop, students more motivated as well as active in following the process of learning.